Effects of agricultural intensity and landscape complexity on plant species richness - Lindström, Sandra (2008)
During the last decades, raised inputs, changed cultivation measures and changes in the farm layout have been implemented in order to raise crop yields. The result has been an intensification of farming with negative consequences for farmland biodiversity. In this study, the impact of different levels of agricultural intensity on plant species richness in winter wheat (Triticum aestivum L.) production has been examined.